Determinants of Household Food Security Based On The Status of Human Development Index (HDI) in the Province of West Nusa Tenggara - Yeyen Anisa Yudita; Khusnul Ashar; Nugroho Suryo Bintoro (Journal of International Conference Proceedings, 2022)
This study aims to determine the determinants or factors that affect household food security in areas with moderate HDI status and areas with high HDI status. Based on the data of the National Socioeconomic Survey (SUSENAS) March 2021 from Statistics Indonesia (BPS), this study is conducted by using multinomial logistic regression method to archieve the objective. The results show that poverty status, dummy recipients of the BPNT program, presence of toilets and presence of toddlers have significant effect to the food security household in areas with high HDI status. While in areas with moderate HDI status, the factors that affect household food security are poverty status, gender of the head of the household, classification of residential area, presence of toilets and presence of toddlers. From this research it is necessary to apply policies that can strengthen household food security in both the moderata HDI and high HDI areas, especially in poor households with toddlers.